(untitled) (African Journal of Biomedical Research, 2024)
Medical wastes such as sharps, infected blood, syringes, body parts and radioactive matters are waste generated during health care service deliveries in hospitals and clinics. Which often receives less attention in developing countries resulting to negative impact on human health due to improper management, and moreover data regarding medical waste management practices are limited in most part of the regions. This research therefore assesses medical waste management and practices in Maiduguri, Borno state, Nigeria. A structured questionnaire, physical observation and key informant interview were used to collect information addressing the generation, segregation, storage, treatment and disposal in 10 selected Heath care facilities across Maiduguri Metropolitan City. From the results Waste generation per bed per month ranges from 16613 kg/bed/month to 324 kg/bed/month, segregation practice was excellent as 77.5% of the respondents had adequate knowledge of waste segregation, However, few (24%) segregated wastes at the point of generation, largely using plastic bins (50%). Knowledge of color coding was satisfactory as 83.75% responded to use color code. Majority (90%) collected waste more than twice/day mainly using plastic bins (46.25%), trolleys (37.5%) and few (12.5%) use combination and plastic and wheel barrows. Personal protective equipment (PPEs) was reported to be used by 98.75% of the respondents. For disposal, medical wastes were mostly burned openly within the hospital (63.75%). In general, the state of medical waste management in Maiduguri was excellent with little challenges of facilities and equipment, the effort of NSHIP (Nigeria-State Health Investment Project) was highly commendable for bridging some gaps.